Mutational analysis in podocin-associated hereditary nephrotic syndrome in Polish patients: founder effect in the Kashubian population - Lipska-Ziętkiewicz, Beata S.; Balasz-Chmielewska, Irena; Morzuch, Lucyna; Wasielewski, Kacper; Vetter, Dominika; Borzecka, Halina; Drozdz, Dorota; Firszt-Adamczyk, Agnieszka; Gacka, Ewa; Jarmolinski, Tomasz; Ksiazek, Joanna; Kuzma-Mroczkowska, Elzbieta; et al. (Journal of applied genetics, 2013)
Hereditary nephrotic syndrome is caused by mutations in a number of different genes, the most common being NPHS2. The aim of the study was to identify the spectrum of NPHS2 mutations in Polish patients with the disease. A total of 141 children with steroid-resistant nephrotic syndrome (SRNS) were enrolled in the study. Mutational analysis included the entire coding sequence and intron boundaries of the NPHS2 gene. Restriction fragment length polymorphism (RFLP) and TaqMan genotyping assay were applied to detect selected NPHS2 sequence variants in 575 population-matched controls. Twenty patients (14 %) had homozygous or compound heterozygous NPHS2 mutations, the most frequent being c.1032delT found in 11 children and p.R138Q found in four patients. Carriers of the c.1032delT allele were exclusively found in the Pomeranian (Kashubian) region, suggesting a founder effect origin. The 14 % NPHS2 gene mutation detection rate is similar to that observed in other populations. The heterogeneity of mutations detected in the studied group confirms the requirement of genetic testing the entire NPHS2 coding sequence in Polish patients, with the exception of Kashubs, who should be initially screened for the c.1032delT deletion.